2008
DOI: 10.1007/s00125-008-1035-7
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of long-chain n-3 fatty acids included in an energy-restricted diet on insulin resistance in overweight and obese European young adults

Abstract: Aims/hypothesis Epidemiological research indicates that long-chain n-3 polyunsaturated fatty acids (LC n-3 PUFA) improve insulin resistance. The aim of this study was to investigate the effects of seafood consumption on insulin resistance in overweight participants during energy restriction. Methods In this 8 week dietary intervention, 324 participants (20-40 years, BMI 27.5-32.5 kg/m 2 , from Iceland, Spain and Ireland) were randomised by computer to one of four energyrestricted diets (−30E%) of identical mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
4
3

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(78 citation statements)
references
References 40 publications
5
66
4
3
Order By: Relevance
“…These findings are consistent with previous studies 49,50) . In wild-type mice, dietary n-3 PUFA but not n-6 GPR120.…”
Section: Epa and Diabetes Mellitussupporting
confidence: 94%
“…These findings are consistent with previous studies 49,50) . In wild-type mice, dietary n-3 PUFA but not n-6 GPR120.…”
Section: Epa and Diabetes Mellitussupporting
confidence: 94%
“…We found no effect of FO on glucose homeostasis and HOMA, which is in line with findings by Pedersen et al (2010) in teenage boys and findings from studies in adults (Egert et al 2008;Giacco et al 2007). In contrast, other studies in adults have observed improved insulin sensitivity as a consequence of fish intake or FO supplementation (Abete et al 2008;Ramel et al 2008).…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have focused upon types of seafood that may be beneficial in preventing MS and possibly reducing the risk of various diseases (8,9). The reduced incidence of CVD among populations consuming fish-rich diets has been attributed to a greater proportion of omega-3 polyunsaturated fatty acids in fish oil (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%